Maximal anaerobic power test in athletes of different sport disciplines - Popadic Gacesa, J. Z.; Barak, O. F.; Grujic, N. G. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to investigate the values of anaerobic energetic capacity variables in athletes engaged in different sport disciplines and to compare them in relation to specific demands of each sport. Wingate anaerobic tests were conducted on 145 elite athletes (14 boxers, 17 wrestlers, 27 hockey players, 23 volleyball players, 20 handball players, 25 basketball players, and 19 soccer players). Three variables were measured as markers of anaerobic capacity: peak power, mean power, and explosive power. The highest values of peak power were measured in volleyball 11.71 ± 1.56 W/kg and basketball players 10.69 ± 1.67 W/kg, and the difference was significant compared with the other athletes (p < 0.05). The lowest value of peak power (8.58 ± 1.56 W/kg) was registered in handball players. The mean power variable showed a similar distribution as peak power among groups. The highest values of explosive power were also registered in volleyball 1.75 ± 0.33 W/s/kg and basketball players 1.64 ± 0.35 W/s/kg, but there was no significant difference in values between volleyball players and wrestlers, between boxers and wrestlers, between boxers and basketball players, and between volleyball and hockey players (p > 0.05). The measured results show the influence of anaerobic capacity in different sports and the referral values of these variables for the elite male athletes. Explosive power presented a new dimension of anaerobic power, i.e., how fast maximal energy for power development can be obtained, and its values are high in all sports activities that demand explosiveness and fast maximal energy production. Coaches or other experts in the field could, in the future, find useful to follow and improve, through training process, one of the variables that is most informative for that sport.